The Impact of Social Distancing on Children and Adolescents and their Long-term Use of the Internet and Technology During COVID-19 Pandemic - Alsaadi, Asma; Alomosh, Ahmad (Al-Adab Journal, 2023)
The Study seeks to remedy the impact of social distancing of children as one of the most important forms of problems that impede the normal and healthy development of children, which affect their behavior and interaction with the outside world significantly. Despite of the variety of the proportions of the children who suffered from social distancing around the world, the impacts of this phenomenon has affected most of the children around the world. The problem of this research is the need to shed some light on the negative consequences that affect various health, psychological and social aspects of children’s and adolescents’ personality, resulted by imposing social distancing or “home quarantine” in an attempt to reduce the outbreak of the Virus, which has negative impacts on children and adolescents in particular. The importance of the Study lies in the fact that this incident is the first of its kind in our era; we have not experienced social distancing and home quarantine imposed on societies because of COVID-19 pandemic and its continuity for a long time, and the importance of the age stage which the research targets, childhood and adolescence, that are pivotal in the life of the individual, where his/her personality is formed and influences the rest of his/her life stages. The findings of the Study show that despite of the significant decrease in the number of infections with COVID-19 the return of life to its normal form, the period of social distancing, which the world spent, resulted negative impacts exceeded the adults while affected the children and adolescents because of the lack of experience. Therefore, the types and forms of that impacts are varied from a child to another, but all scientists, researchers and doctors agree unanimously that there is a gap in the personality of children. The proposals and recommendations affirm the importance to unite all the concerned individuals and parties about dealing with children and adolescents, such as families, schools, universities, media establishments, Ministry of Health and society in order to implement treatment plans and disseminate the necessary awareness to ensure overcoming the negative impacts which affected the children and adolescents during the period of social distancing.